Vivenciando a transição para a universidade durante a pandemia de COVID-19: um estudo de photovoice sobre as expectativas dos calouros de 2020 - Gomes, Letícia de Paula (Universidade Federal de São Carlos, 2023)
This Course Conclusion Paper is a composition of the Scientific Initiation research "Active expectations in quarantine mode": photographs that reveal personal expectations and experiences with social isolation, imposed by the new coronavirus pandemic", developed within the ICT registration period from September/2020 to September/2021, and its unfoldings that resulted in occupational therapeutic reflections on the results and the production of an article. Initially, the research had as its main objective to propose a reflection on the experiences lived by freshmen entering UFSCar in 2020, during the isolation period imposed by the COVID-19 pandemic, and its impacts on expectations regarding professional choice and future. For this, the resource of photography was used, from the Photovoice strategy, which allows us to capture the different experiences and perceptions of the participants of a research in question. Four meetings were held, with different triggering themes, in order to approximate the experiences lived by the students using a visual resource, considering the particularities of the atypical moment we are still experiencing.
Experiencing the transition to college during the COVID-19 pandemic: a photovoice study of 2020 freshman expectations
Keywords: Saúde mental; Isolamento social; Fotografia; Universidade; CIENCIAS DA SAUDE::MEDICINA::PSIQUIATRIA